Q: Simplify 9a plus 8 minus 2a minus 3 minus 5a?

Write your answer...

Submit

Related questions

2a + 11a - 5a = 8a

Add them together: 2a+5a = 7a

2a-5

2a² + 6a

2a + 10 + 5a - 2 = (2a + 5a) + (10 - 2) = 7a + 8

2a + 4b

5a³ - 4ab + 2a³ = (5+2)a³ - 4ab = 7a³ - 4ab.

5a + 11

2a

(5a+8) - (2a+4) =3a +4 To do this, simply subtract like terms. 5a-2a=3a and 8-4=4

6+7a+6b

2a + 3a + 4 = 5a + 4

2a+5a+9a = 16a

2a + 5a + 3a = 10a

3a4 - 2a2 + 5a - 10 - 2a4 + 4a2 + 5a - 2 = a4 + 2a2 + 10a - 12 = a4 + (2a - 2)(a + 6)

9a +8 -2a -3 -5a = 2a +5

2

The value of a in the equation 5a plus 2a = 6-6a is a=6/11.

5a + 3 + (2a - 2) + a= 5a + 3 + 2a - 2 + a= 8a + 1

2a + 3a = 5a

-7a+2a+9 is also -5a+9. -5a+9=24. -5a=15. a=-3.

3a + 2a = 5a

5a- 2a = 3

If: 2a+13 = 5a+1 Then: a = 4

2a - 5a = -3a

Study guides